Credit Market Structure and Collateral in Rural Thailand. (12th June 2017) - Kislat, Carmen; Menkhoff, Lukas; Neuberger, Doris
Abstract : This paper empirically examines reliance on collateral in different credit market segments—formal, semiformal and informal lending—of a developing rural financial market. Determinants of collateralization indicate that all three types of lenders price risk conventionally. Controlled for standard risk factors, however, formal lenders rely on collateral about 40 per cent more often than informal lenders. The difference is explained by informal lenders' better information on borrowers. This is shown by informal lenders' behaviour: a longer lending relationship does not improve information about the borrower but shorter distance to the borrower does—the opposite applies to formal lenders, as predicted by theory.